PENGUATAN REGULASI DALAM PENCEGAHAN DAN PENANGGULANGAN PERKAWINAN ANAK - Nazli, Nurnazli (Indonesian Association of Islamic Family Law Lecturers, 2019)
This article elaborates on solutions to promote and strengthen the regulation preventing child marriage practices in Indonesia, so the purpose of marriage that to create a happy and eternal family will be created based on the One True God. The equality paradigm in determining the minimum age of marriage has been realized by the Indonesian Government by raising Law No. 16 of 2019 on Amendment to Law No 1 of 1974 on Marriage. Article 7 paragraph (1) on the Post Revised Marriage Law explains that the minimum age for a marriage is 19 years and no age difference between spouses (men and women). The purpose of the Act is the Indonesian government can be more serious in minimizing the child marriages that still happen today. This research found that the following steps can strengthen the regulation preventing child marriage. First, create intense communication within the family. Secondly, it involves the judiciary in the context of enforcing rules regarding the age limit of marriage. Third, the Supreme Court must immediately make rules that can complicate marriage dispensation. Fourth, providing socialization related to the rule of law regarding the minimum age for marriage and counseling about the negative effects of child marriage. Fifth, open opportunities for adolescents to develop their potential, so that the gap in the child marriage can be minimized. To realize these steps, the government, parents and the community must work together in accordance with their respective capacities.